THROUGHPUT IMPROVEMENT AND COMPARATIVE PERFORMANCE ANALYSIS OF INTEGRATED NETWORKS - Obazee, Nosakhare Jeffrey (My University, 2020)
The demand for high-speed communication continue to increase significantly. Industry forecasts have shown that future data services would contribute to rapid growth in data traffic, with most of this traffic primarily indoors and at hotspots locations. Thus, the deployment and integration of small cell base stations (SCBSs) with Wireless Local Area Network (WLAN) or Wi-Fi is viewed as a critical solution to offload traffic, maximize coverage and boost future wireless systems capacity. This thesis reviews the existing network of WLAN, Long Term Evolution (LTE) and Worldwide Interoperability for Microwave Access (WiMAX). Tight and Loosely coupled integration of these networks is studied. More specifically, the introduction of small cell (SC) in loosely coupled Wi-Fi /WiMAX and Wi-Fi/LTE are proposed. These designs are tested in real-time user experience applications consisting of video conferencing, hypertext transfer protocol (HTTP) and email using industrial simulation software, Riverbed Modeler 18.7. Quality of service parameters was used to analyze these networks. It was found that the throughput of loosely coupled Wi-Fi/WiMAX network can be optimized by small cell. The loosely coupled architecture of Wi-Fi/WiMAX small cell outperforms that of Wi-Fi/LTE small cell. The loosely coupled independently deployed network of Wi-Fi/LTE small cell performs better than the Wi-Fi network. The Wi-Fi/LTE small cell network achieved a substantial rise in downlink throughput in a network consisting of only video conferencing subscriber stations
Keywords: mobile communication networks; wireless networks; wireless communication; base stations; wireless technology; fi=Tietoliikennetekniikka|en=Telecommunications Engineering|; Master’s Programme in Wireless Industrial Automation